Photodynamic therapy in the treatment of drug-induced osteonecrosis: a case report - Araújo Santos, Rodrigo (2021)
The main of this case was to investigate the benefits of photodynamic therapy (PDT) in application cycles as a method of treatment of medication-related osteonecrosis of the jaw (MRONJ), reporting the case of a 75-year-old white male patient with a diagnosis of renal malignancy with lung and bone metastases treated with sunitinib malate and denosumab. The patient was referred for dental evaluation in an office set up to attend patients with special needs, in the city of Salvador-Ba. In the intraoral examination, areas of exposed and necrotic bone tissue were observed in the mandible (medial aspect) on both sides, close to the molar region, with an ulcerative appearance, three millimeters in diameter, and the diagnostic hypothesis was stage 2 ONMRM The application protocol of 20 PDT cycles was started, as the only form of treatment, in two weekly sessions with preventive laser therapy for oral mucositis. During and at the end of the treatment, necrotic bone sequestration was possible, promoting biostimulation and locoregional healing, without clinical manifestation of the pathology during maintenance. Based on this report and the evidence in the scientific literature, it is believed that clinical trials should be promoted, due to the promising and effective records of the treatment that the therapy makes possible.